BETWEEN EFFICACY AND RISK: A CRITICAL APPRAISAL OF METAMIZOLE’S PHARMACOLOGY, CLINICAL USE AND REGULATORY STATUS - Julia Maszewska; Szymon Milnerowicz; Paulina Rzepa; Łukasz Brzost; Marta Danuta Cendrowska; Beata Choromańska; Julia Procyk; Justyna Berent; Karolina Stępień; Barbara Ponitka; Aleksandra Klukowska; Wiktoria Szumlińska (International Journal of Innovative Technologies in Social Science, 2025)
This review critically assesses metamizole’s pharmacology, clinical efficacy, and safety profile, with particular focus on its widespread over-the-counter (OTC) availability in Poland versus more restrictive approaches elsewhere. The primary research objective was to evaluate whether the clinical benefits of metamizole outweigh its well-documented risks, especially severe adverse effects such as agranulocytosis and immune-mediated liver injury. During the research PubMed, Google Scholar, and institutional sources were used, applying keywords: “pyralgin,” “metamizole,” “analgesic,” “side effects,” “synergy,” and “combination”. Publications from 2000 to 2025 were screened for relevance, with a primary focus on articles in English and Polish. Abstracts were initially analyzed, followed by full-text review; 20 pertinent sources were ultimately selected for appraisal, comparing indications, mechanisms, and interactions with other analgesics, notably paracetamol, NSAIDs, opioids, and gabapentin. Findings demonstrate that metamizole shows unique spasmolytic, analgesic, and antipyretic properties, and offers therapeutic synergism with various analgesic combinations, aiding multimodal pain management when minimizing opioid or NSAID use is preferred. However, serious adverse events, while infrequent, are potentially fatal and unpredictable, with no effective preventive measures or reliable individual risk prediction identified. The review concludes that the unrestricted OTC availability and mass media promotion of metamizole pose disproportionate public health risks. It recommends limiting access to prescription-only status and ending promotional advertising for common ailments, given the availability of safer first-line analgesics.